VARIAÃ‡ÃƒO DIÃRIA EM ALGUNS FATORES DE UM SISTEMA LÃMNICO - Piccolo, A. L. G.; Cunha, R. A.; Bueno, O.; Gama, V.; Zaine, J. Farid; Baldoni, E. L.; Gagheggi, V. M.; Chaddad, E. (REVISTA DE AGRICULTURA, 2016)
VARIAÃ‡ÃƒO DIÃRIA EM ALGUNS FATORES DE UM SISTEMA LÃMNICO